Single Stage Endovascular Treatment of a Type 2 Abernethy Malformation: Successful Nonsurgical Outcome in a Case Report - Carl Kraus; Vladimir Sheynzon; Robert Hanna; Joshua Weintraub (Case Reports in Radiology)
Abernethy malformations are a rare collection of congenital hepatic portosystemic shunts. Our 19-year-old patient is with a type 2 Abernethy malformation elected permanent shunt closure following worsening dyspnea. This report details a single stage endovascular technique wherein shunt closure was achieved immediately by placement of an aortic endograft. At 5-month follow-up, the patient reported decreased shortness of breath. Furthermore, ultrasound investigation demonstrated a patent portal vein and right heart catheterization 6 months after procedure revealed decreased pulmonary hypertension relative to preprocedure values. This one step method may serve as an alternative treatment strategy to multistage endovascular closure techniques of type 2 Abernethy malformations.